Molecular Cloning and Functional Characterization of Two Brachypodium distachyon UBC13 Genes Whose Products Promote K63-Linked Polyubiquitination - Guo, Huiping; Wen, Rui; Liu, Zhi; Datla, Raju; Xiao, Wei (Frontiers in Plant Science, 2016)
Living organisms are constantly subject to DNA damage from environmental sources. Due to the sessile nature of plants, UV irradiation is a major genotoxic agent and imposes a significant threat on plant survival, genome stability and crop yield. In addition, other environmental chemicals can also influence the stability of the plant genome. Eukaryotic organisms have evolved a mechanism to cope with replication-blocking lesions and stabilize the genome. This mechanism is known as error-free DNA damage tolerance, and is mediated by K63-linked PCNA polyubiquitination. Genes related to K63-linked polyubiquitination have been isolated recently from model plants like Arabidopsis and rice, but we are unaware of such reports on the crop model Brachypodium distachyon. Here we report the identification and functional characterization of two B. distachyon UBC13 genes. Both Ubc13s form heterodimers with Uevs from other species, which are capable of catalyzing K63 polyubiquitination in vitro. Both genes can functionally rescue the yeast ubc13 null mutant from killing by DNA-damaging agents. These results suggest that Ubc13-Uev-promoted K63-linked polyubiquitination is highly conserved in eukaryotes including B. distachyon. Consistent with recent findings that K63-linked polyubiquitination is involved in several developmental and stress-responsive pathways, the expression of BdUbc13s appears to be constitutive and is regulated by abnormal temperatures.